Renoprotective effects of ACE inhibitors on the progression of diabetic kidney disease - Mochammad Sja'bani Mochammad Sja'bani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Functional and structural abnormalities in diabetic kidney disease lead to intraglomerular hypertension and albuminuria. Systemic hypertension and genetically inherited defect on autoregulation in preglomerular arterioles will enhance kidney injury in those patients. ACE inhibitors could reduce albuminuria In patients with diabetic nephropathy and animal models. Hemodynamic improvement manifested by the reduction of albuminuria by ACE inhibitors is only seen in the experimental studies. However, recent studies have shown that ACE inhibitors, especially captopril, could give protective effects on kidneys in insulin-dependent diabetics with nephropathy. Captopril also reduces the risk of death, dialysis, and kidney transplantation in those patients.Key words: diabetes mellitus -- kidney disease -- ACE inhibitors -- albuminuria -- kidney preservation